Aspek-aspek Pembaruan Hukum Islam dalam Hukum Keluarga di Indonesia - Fitriyani, Fitriyani (Tasamuh: Jurnal Studi Islam, 2019)
Islamic law reform is essentially contrary to something that already exists (existing) then undergo a qualitative change as a product of interaction in public life It could be argued that the process of law reform Islam is seen as something autonomous, but he also interacts with other elements in society that occurred interdependent. Therefore, the concept of renewal of Islamic law requires adaptatif stance with social conditions in which it interacts. In this case, the realization of the principle of al-muhafadzah 'ala al-qadim wa al-Salih al-akhdzu bi al-jadidi al-ashlah (maintaining the old one if it is still good and accept the new or changed if it is considered better), became a necessity. Within the framework of family law reform Indonesia, Islamic law meempunyai a very important role and strategic. Said, because the family law of Islam. in addition to recognized as a source of juridical law, also has universal principles and in accordance with the personality of the Indonesian nation. In fact, sociologically Islamic family law has taken root and become law who live in the midst of the majority of Indonesian people. Renewal of Islamic law in the context of family law Indonesia includes four categories, namely; jurisprudence, fatwa, jurisprudence and legislation.